Physiological Effects of Aqueous Myristica fragrans Extract on Lipid Profiles, Oxidative Stress, and Organ Function in Hyperlipidemic Male Albino Rats: Efek Fisiologis Ekstrak Myristica fragrans Berair pada Profil Lipid, Stres Oksidatif, dan Fungsi Organ pada Tikus Albino Jantan Hiperlipidemia - Nasir, Kawther Mohammed (Indonesian Journal on Health Science and Medicine, 2024)
Hyperlipidemia is a leading risk factor for cardiovascular diseases and metabolic disorders, often exacerbated by high-fat diets. This study evaluates the physiological effects of aqueous Myristica fragrans (nutmeg) extract on hyperlipidemia-induced male albino rats. A total of 30 rats were divided into four groups: a control group, a high-fat diet group, a high-fat diet supplemented with 50 mg/kg nutmeg extract, and a nutmeg-only group. Over a month, lipid profiles, glucose levels, oxidative stress markers, and liver and kidney functions were assessed, nutmeg extract significantly reduced blood glucose levels from 188.5 mg/dL in the high-fat diet group to 124.25 mg/dL in the treated group (p < 0.05). Oxidative stress markers showed notable improvement, with malondialdehyde (MDA) levels decreasing from 2.94 μmol/L in the high-fat diet group to 1.43 μmol/L in the treated group. However, glutathione (GSH) levels decreased to 1.74 μmol/L in the treated group compared to 2.34 μmol/L in controls, indicating a selective antioxidant response. Lipid profile analysis revealed mixed results; triglycerides increased to 134.53 mg/dL in the treated group, suggesting limited lipid-lowering effects. Notably, liver function tests indicated hepatotoxic effects in the nutmeg-only group, with ALT levels rising to 142.17 mg/dL (control: 101.2 mg/dL), warranting caution for standalone use. Kidney function remained relatively stable, with creatinine levels unaffected, but urea levels increased to 68.87 mg/dL in the high-fat diet group with nutmeg supplementation. The findings suggest that nutmeg extract has promising hypoglycemic and antioxidant properties but limited efficacy in improving lipid profiles and potential risks to liver health. Further research is recommended to optimize dosage and evaluate long-term safety for clinical applications in managing hyperlipidemia. Highlights: Hypoglycemic Effects: Nutmeg extract reduced blood glucose levels significantly (188.5 → 124.25 mg/dL). Antioxidant Properties: Improved oxidative stress markers but decreased glutathione levels selectively. Risks: Limited lipid-lowering effects; potential hepatotoxicity observed in nutmeg-only group. Keywords: Myristica fragrans, hyperlipidemia, Lipid Profiles, Oxidative Stress, and Organ , Albino Rats